Quality Assurance for Chemistry and Environmental Science Metrology from pH Measurement to Nuclear Waste Disposal - Meinrath, Günther; Schneider, Petra (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Metrological concepts like traceability or measurement uncertainty form important parts of international treaties and normative documents. Their applications e.g. in chemical or food analysis or in environmental monitoring are entering our daily life. The development of those concepts has been driven by demand on a world-wide scale from trade, industry and the legal systems. In the future, no chemist, geochemist, chemical , civil or environmental engineer and no other specialist dealing with chemical measurement data, and no decision maker, neither in trade and industry, in public or medical services, in the political and diplomatic arenas or in academic research can afford not to become acquainted with metrology, its concepts and impact. This book provides a basic overview over the relevant metrological concepts like traceability, ISO uncertainties or cause-and-effect diagrams. The applications described in great detail range from progression-of-error type evaluation of the measurement uncertainty budget to complex applications like pH measurement or speciation calculations for aqueous solutions. The consequences of a measurement uncertainty concept for chemical data are outlined for geochemical modeling applied to transport in the subsurface and to nuclear waste disposal. Special sections deal with the deficits of existing thermodynamic data for these applications and with the current position of chemical metrology in respect to other quality assurance measures, e.g. ISO 900x, GLP, European and U.S.-American standards.  .